Estudio comparativo de cuatro métodos de extensión en El Salvador - Pereira de Melo, G. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Four extension methods, meetings, visits, method demonstrations, leaders, were compared in teaching an agricultural practice, vaccination of cattle against antrax. Sixty members of six 4-C boy clubs of Ilobasco, El Salvador, 13–15 years old, were selected to measure the quantity of knowledge they had, both before and after the application of the methods. Results show that there was a large increase in knowledge between the pre-and final tests. Meetings and visits were better than method demonstration and leaders. There was no difference between meetings and visits nor between demonstration and leaders. They were similar in behaviour when compared in pairs.